2018
DOI: 10.1101/372110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

State-specific individualized functional networks form a predictive signature of brain state

Abstract: There is extensive evidence that human brain functional organization is dynamic, varying within a subject as the brain switches between tasks demands. This functional organization also varies across subjects, even when they are all engaged in similar tasks. Currently, we lack a comprehensive model that unifies the two dimensions of variation (brain state and subject). Using fMRI data obtained across multiple task-evoked and rest conditions (which we operationally define as brain states) and across multiple sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
(99 reference statements)
1
4
0
Order By: Relevance
“…In the literature of brain parcellation, the only approach that had consistent findings with our approach was published by Salehi and colleagues [6,40] . We both suggested an approach that contradicts the notion of a fixed functional parcellation of the brain.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the literature of brain parcellation, the only approach that had consistent findings with our approach was published by Salehi and colleagues [6,40] . We both suggested an approach that contradicts the notion of a fixed functional parcellation of the brain.…”
Section: Discussionsupporting
confidence: 58%
“…Even though dynamic functional connectivity is well studied, to the best of our knowledge, the only parcellation approach that considered dynamic changes of parcels was suggested by Salehi and colleagues. These authors demonstrated that the brain functional parcellations are not spatially fixed, but reconfigure with task conditions [6,40] . These reconfigurations were used to reliably predict different task conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Publicly available ROIs enhance comparability with other groups and minimize the bias of manually selecting components from our small sample. On the other hand, previous work demonstrated that sample-and task-specific parcellation was more functionally relevant (Dickie et al, 2017;Geerligs et al, 2017;Salehi et al, 2017Salehi et al, , 2018. To achieve a balance between sensitivity and specificity, a three-step methodology was used, combining a sample analysis of the task main effect along with spatial and time mapping with CONN parcellation.…”
Section: Roi Definitionmentioning
confidence: 99%
“…ICA can provide multiple spatially overlapping components and these can be allowed to vary with condition. These ICA components are often few in number (30–70) and may not be spatially contiguous and share more in common with network analyses rather than node analyses ( Salehi et al, 2018 ; Smith et al, 2011 ). In the gradient work ( Margulies et al, 2016 ; Vázquez-Rodríguez et al, 2019 ) principal axes have been investigated and in some cases these have been shown to vary with task ( Tian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%